Optimization of the Minimum Mining Unit for Short-Term Planning (Research, Society and Development, 2022)
In open pit mining, in the short term, the mining plans are subdivided into quarterly, monthly, weekly and daily operations. Monthly, the short-term planner defines the polygons, which comprise successive mining advances. These ore quality and tonnage parameters are previously determined by the mill. Traditionally, traverses are designed without a proper systematic approach. The interactions performed to obtain the specifications required by the plant are limited. There is a demand for studies involving optimization techniques for minimum mining units, helping the design of the ore, in order to minimize the variability in grade and maximize the recovery of the plant. This article proposes the adaptation of two optimization algorithms – Floating Cone and Floating Stope, traditionally used to define underground pits and highlights. A dimension value equal to zero was assigned to the support pillars, approaching the chambers and pillars method to a bench method, to configure a behavior close to open pit mining. The study proved that both methodologies presented satisfactory results. Despite the need for manual adjustments, discarding shared blocks, the Floating Cone proved to be a more selective system, especially for higher cut grades.